Thermal stability, antioxidant, and anti-inflammatory activity of curcumin and its degradation product 4-vinyl guaiacol. Issue 3 (11th March 2015) - Esatbeyoglu, Tuba; Ulbrich, Katrin; Rehberg, Clemens; Rohn, Sascha; Rimbach, Gerald
<x xml:space="preserve">Abstract</x> The curcumin degradation product 4-vinyl guaiacol exhibits biological activity.